The Effect of STEAM Learning on Improving Each Indicator of Students' Creative Thinking in Physics Learning - Tasta Witdiya; Gito Supriadi; Atin Supriatin; Jhelang Annovasho (Jurnal Ilmiah Pendidikan Fisika, 2023)
The research aims to analyze the effectiveness toward which STEAM learning improves each indication of students' creative thinking ability in physics learning. This research used a quantitative approach with a quasi-experimental design and a non-equivalent pretest-posttest control group design. In this research, the Class XI science students of SMA Negeri 1 Mentaya Hilir Utara during the 2022-2023 school year would present as the population. Class XI IPA I was selected as the experimental class, while class XI IPA II was presented as the control class in the sample. The collected research data will be analyzed using the Willcoxon test, the Mann-Whitney difference test, and the N-gain test. The improvement (N-Gain) of all indicators has reached the moderate category. Indications in the element of elaboration increased the highest, while indicators in the aspect of originality increased the lowest. Based on the improvement in each indicator and the results of regression tests on each indicator, it is demonstrated that STEAM learning has a very favorable effect on students' creative thinking abilities. STEAM-based learning is recommended for usage as an innovation in physics learning in schools in order to develop creative thinking.